2017
DOI: 10.3389/fphys.2017.00656
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Athletic Development in Youth Alpine Ski Racing: The Effect of Physical Fitness, Ski Racing Technique, Anthropometrics and Biological Maturity Status on Injuries

Abstract: Alpine ski racing is known to be a sport with a high risk of injuries. Because most studies have focused mainly on top-level athletes and on traumatic injuries, limited research exists about injury risk factors among youth ski racers. The aim of this study was to determine the intrinsic risk factors (anthropometrics, biological maturity, physical fitness, racing technique) for injury among youth alpine ski racers. Study participants were 81 youth ski racers attending a ski boarding school (50 males, 31 females… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
54
5
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(69 citation statements)
references
References 56 publications
(99 reference statements)
4
54
5
5
Order By: Relevance
“…The biological maturity status, changes in anthropometric characteristics and physical fitness over one season as well as traumatic and overuse injuries were recorded. A sport specific internet-based database was developed and used in the present study; the database was reported by Müller et al [6]. All tests were performed in the laboratory of the Department of Sport Science by experienced researchers.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The biological maturity status, changes in anthropometric characteristics and physical fitness over one season as well as traumatic and overuse injuries were recorded. A sport specific internet-based database was developed and used in the present study; the database was reported by Müller et al [6]. All tests were performed in the laboratory of the Department of Sport Science by experienced researchers.…”
Section: Methodsmentioning
confidence: 99%
“…A decreased neuromuscular control of the knee was found to predict the risk of sustaining an ACL injury in female athletes [9]. Additionally, 10 to 14 year old youth ski racers with less pronounced anthropometric characteristics (weight, height, sitting height), and late maturing athletes were more vulnerable for more severe injuries (based on time-loss-definition) [6] and ski racers with high differences in unilateral isometric leg extension strength between the left and the right leg were at a higher risk of sustaining traumatic injuries in general, and most probably knee injuries [7]. Training load characteristics, such as training volume or intensity, among others, do not seem to influence the injury risk of youth ski racers [10].…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations